Hormetic Effect of Glyphosate on the Morphology, Physiology and Metabolism of Coffee Plants - Costa, Renato Nunes [UNESP]; Bevilaqua, Natalia da Cunha [UNESP]; Krenchinski, Fábio Henrique [UNESP]; Giovanelli, Bruno Flaibam [UNESP]; Pereira, Vinicius Gabriel Caneppele [UNESP]; Velini, Edivaldo Domingues [UNESP]; Carbonari, Caio Antonio [UNESP] (MDPI, 2023)
Glyphosate is a nonselective herbicide of systemic action that inhibits the enzyme 5-enolpyruvylshikimate-3-phosphate synthase, thus compromising amino acid production and consequently the growth and development of susceptible plants. The objective of this study was to evaluate the hormetic effect of glyphosate on the morphology, physiology, and biochemistry of coffee plants. Coffee seedlings (Coffea arabica cv Catuaí Vermelho IAC-144) were transplanted into pots filled with a mixture of soil and substrate and subjected to ten doses of glyphosate: 0, 11.25, 22.5, 45, 90, 180, 360, 720, 1440, and 2880 g acid equivalent (ae) ha−1. Evaluations were performed using the morphological, physiological, and biochemical variables. Data analysis for the confirmation of hormesis occurred with the application of mathematical models. The hormetic effect of glyphosate on coffee plant morphology was determined by the variables plant height, number of leaves, leaf area, and leaf, stem, and total dry mass. Doses from 14.5 to 30 g ae ha−1 caused the highest stimulation. In the physiological analyses, the highest stimulation was observed upon CO2 assimilation, transpiration, stomatal conductance, carboxylation efficiency, intrinsic water use efficiency, electron transport rate, and photochemical efficiency of photosystem II at doses ranging from 4.4 to 55 g ae ha−1. The biochemical analyses revealed significant increases in the concentrations of quinic acid, salicylic acid, caffeic acid, and coumaric acid, with maximum stimulation at doses between 3 and 140 g ae ha−1. Thus, the application of low doses of glyphosate has positive effects on the morphology, physiology, and biochemistry of coffee plants.
Keywords: growth stimulation; hormesis; photosynthesis; shikimic acid pathway; underdoses